Core-shell TiO2@HfO2 nanowire arrays with designable shell thicknesses for improved permittivity and energy density in polymer nanocomposites. (October 2020) - Chen, Sheng; Zhou, Yang; Luo, Hang; Tang, Lin; Guo, Ru; Zhang, Dou
Highlights: Core-shell TiO2 @HfO2 Nanowire Arrays were prepared by atomic layer deposition (ALD) method. The HfO2 shell thicknesses were regulated via controlling the cycle times of ALD and increased from 2.4 nm to 5.4 nm with the increase of the cycle times from 13 times to 50 times. The permittivity and energy density of the nanocomposites increased monotonously with shell thicknesses. Abstract: In this paper, core-shell structured TiO2 @HfO2 nanowire arrays with designable HfO2 layer thicknesses were constructed by atomic layer deposition (ALD) method. The effects of TiO2 @HfO2 nanowire arrays filler and HfO2 thickness on dielectric and energy storage properties of polyvinylidene fluoride (PVDF) based nanocomposites were investigated. The HfO2 shell thicknesses were controlled via regulating the cycle times of ALD and increased from 2.4 nm to 5.4 nm with the cycle times increment from 13 times to 50 times. Owing to the ferroelectricity of the HfO2 and the hierarchical interfacial polarization originated from the multilevel interface in the composites, the permittivity of the TiO2 @HfO2 nanowire array/PVDF nanocomposite with 50 deposition cycles reached 27.4 at 10 3 Hz, which was 105% larger than that of the TiO2 nanowire array/PVDF nanocomposite. Moreover, the maximal discharged energy density is 2.92 J/cm 3 at a low electric field of 138 kV/mm, exceeding more than 97%.